PENGEMBANGAN MEDIA INTERAKTIF WORDWALL TERHADAP MOTIVASI BELAJAR IPAS PESERTA DIDIK KELAS IV SEKOLAH DASAR - Aurila, Angel Aurila; Arita Marini; Waluyo Hadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study develops a Wordwall-based learning media with a Maze Runner theme for the Natural and Social Sciences (IPAS) subject, in which students answer questions through a maze containing answer choices; correct answers unlock the route to the next question, while incorrect answers close the route. Validation results indicate a media feasibility score of 96% and a content feasibility score of 85%, both categorized as highly feasible. A limited field trial conducted with 6 fourth-grade students at SDN Susukan 08 Pagi yielded a response percentage of 79.5% (feasible), while a broader field trial involving 12 students obtained a percentage of 83.1% (highly feasible), with recommendations for improvement regarding the maze display, visual effects, and answer distractors. This media is deemed suitable for use as an interactive learning alternative in IPAS instruction.